Analysis of Starch Distribution in the Paper Cross-Section by Raman Microscopy. Issue 1 (January 2013) - Pigorsch, Enrico; Finger, Matthias; Thiele, Steffen; Brunner, Eike
A new Raman microscopy approach was developed to analyze the starch distribution of paper cross-sections in a faster and more specific way than is possible with the currently used iodine-staining method. Raman images were recorded and analyzed from cross-sections of cellulose hand sheets surface-sized with 1% or 2% starch solutions and with different film thicknesses. In addition, Raman imaging analysis of the starch distribution was performed on two industrial papers, an abrasive base paper and a surface-sized recycling paper. The visualization and the quantitative analysis of the starch distribution were performed by using the intensity changes of the Raman starch band at 855 cm −1 and by principal component analysis. Distribution curves were calculated from the intensity data and compared for the samples with different starch concentrations and with results obtained from iodine-stained crosssections of the same samples. The results of this study demonstrate the great potential and the new possibilities of Raman microscopy for studying the z -distribution of chemical components and additives in paper.